2012
DOI: 10.1016/j.cell.2012.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Paternal RLIM/Rnf12 Is a Survival Factor for Milk-Producing Alveolar Cells

Abstract: In female mouse embryos, somatic cells undergo a random form of X chromosome inactivation (XCI), while extraembryonic trophoblast cells in the placenta undergo imprinted XCI, silencing exclusively the paternal X chromosome. Initiation of imprinted XCI requires a functional maternal allele of the X-linked gene Rnf12 which encodes the ubiquitin ligase Rnf12/RLIM. Here we find that knockout (KO) of Rnf12 in female mammary glands inhibits alveolar differentiation and milk production upon pregnancy. Alveolar cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…1B). MMTV-Cre is also expressed in the embryonic epidermis (Jiao et al, 2012) and, as expected, itgb4 -deleted tissue exhibited a loss of β4 staining in the skin (Fig. 1B).…”
Section: Resultssupporting
confidence: 78%
“…1B). MMTV-Cre is also expressed in the embryonic epidermis (Jiao et al, 2012) and, as expected, itgb4 -deleted tissue exhibited a loss of β4 staining in the skin (Fig. 1B).…”
Section: Resultssupporting
confidence: 78%
“…In mouse mammary epithelial cells, X-chromosome inactivation is not random but is preferentially maternally inactivated (Jiao et al, 2012). Interestingly, the X-linked gene ring finger protein 12 (Rnf12), which encodes the ubiquitin ligase Rnf12/RLIM, is a critical survival factor for milk-producing alveolar cells (Jiao et al, 2012).…”
Section: Imprinting In the Mammary Glandmentioning
confidence: 99%
“…Interestingly, the X-linked gene ring finger protein 12 (Rnf12), which encodes the ubiquitin ligase Rnf12/RLIM, is a critical survival factor for milk-producing alveolar cells (Jiao et al, 2012). In humans, limited studies of gene expression in the breast have similarly demonstrated monoallelic expression of growth and survival factors in normal breast tissues.…”
Section: Imprinting In the Mammary Glandmentioning
confidence: 99%
“…In mouse mammary epithelial cells the maternal X chromosome is non-randomly silenced (Jiao et al, 2012). In humans monoallelic expression of Igf2 by mammary epithelium is the norm (Yun et al, 1999).…”
Section: Lactationmentioning
confidence: 99%